Management of Melaleuca by Residents in South Florida - Katherine Carter-Finn; Alan W. Hodges; Donna J. Lee; Michael T. Olexa (EDIS)
FE672, a 6-page fact sheet by Katherine Carter-Finn, Alan W. Hodges, Donna J. Lee, and Michael T. Olexa, describes the results of a survey of a random sample of households in the 10 southernmost counties of Florida. Includes references. Published by the UF Department of Food and Resource Economics, November 2006.